2020
DOI: 10.1016/j.molcel.2019.10.022
|View full text |Cite
|
Sign up to set email alerts
|

RNA-RNA Interactomes of ProQ and Hfq Reveal Overlapping and Competing Roles

Abstract: Highlights d RNA-RNA interactomes for RNA chaperones ProQ and Hfq are identified by RIL-seq d A significant fraction of the RNA-RNA pairs on ProQ also are found on Hfq d sRNA-mediated regulation is impacted by growth conditions d ProQ blocks RNase III-and Hfq-mediated downregulation by a novel sRNA sponge

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
390
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(402 citation statements)
references
References 66 publications
12
390
0
Order By: Relevance
“…We wondered whether the ProQ-cspE B3H interaction might be limited by competition with endogenous ProQ or cellular Hfq, given that co-immunoprecipitation studies have suggested that ProQ and Hfq may compete for a subset of their RNA substrates. (22,37) While no additional stimulation of transcription over basal levels was observed when the ProQ-cspE B3H experiment was repeated in ΔproQ reporter cells ( Fig 1C; 1.2), we found that the fold-stimulation of β-gal transcription indeed increased in Δhfq reporter cells ( Fig 1D; 2.3x). This Δhfq reporter strain was previously used for detecting Hfq-RNA interactions, (30) and was used throughout the remainder of this study.…”
Section: Establishing a B3h Assay For Proq-rna Interactionsmentioning
confidence: 67%
See 3 more Smart Citations
“…We wondered whether the ProQ-cspE B3H interaction might be limited by competition with endogenous ProQ or cellular Hfq, given that co-immunoprecipitation studies have suggested that ProQ and Hfq may compete for a subset of their RNA substrates. (22,37) While no additional stimulation of transcription over basal levels was observed when the ProQ-cspE B3H experiment was repeated in ΔproQ reporter cells ( Fig 1C; 1.2), we found that the fold-stimulation of β-gal transcription indeed increased in Δhfq reporter cells ( Fig 1D; 2.3x). This Δhfq reporter strain was previously used for detecting Hfq-RNA interactions, (30) and was used throughout the remainder of this study.…”
Section: Establishing a B3h Assay For Proq-rna Interactionsmentioning
confidence: 67%
“…Given that ProQ has been found to interact with dozens of sRNAs and hundreds of mRNAs inside of Salmonella and E. coli cells, (17) we sought to determine whether our B3H system could detect ProQ interactions with additional RNAs beyond cspE. We tested three additional RNAs that had been found to interact in vivo with ProQ: sRNAs SibB, RyjB and the 3'UTR of fbaA (hereafter, fbaA); (17,22,37) as well as four sRNAs for which we had previously detected B3H interactions with Hfq: ChiX, OxyS, ArcZ, and MgrR ( Fig S3). (30) While a cspE hybrid RNA consistently produced the highest stimulation of transcription above basal levels when present with α-ProQ Δ CTD , we observed a ≥1.5-fold increase in fold-stimulation of β-gal activity when each of these hybrid RNAs was present in reporter cells (Fig 2A; full b-gal data in Fig S4A).…”
Section: Scope Of Detectable Rna Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Global identification of new RNA/protein interactions has been enabled by deep-sequencing approaches (7), such as Grad-seq, which uses glycerol gradients to identify novel RNA/protein complexes (8), CLIP-seq, which uses crosslinking to define protein binding sites in the transcriptome (9), and RIL-seq which identifies protein-dependent RNA-RNA interactions (10). Recent studies using these approaches showed that another protein, named ProQ, is a global RNA binding protein in Escherichia coli and Salmonella enterica (11-13), and is involved in sRNA interactions with other RNA molecules (12,14,15). The pool of RNA ligands of ProQ is mostly distinct from that of Hfq and contains more mRNAs than sRNAs (11,12).While ProQ was originally discovered in a search for genes that affect proline transport (16), this protein contributes to several physiological processes in E.coli and S. enterica (17)including DNA metabolism (13,14), bacterial virulence (15), and adaptation to osmotic stress (12) and resource limitation (18).…”
mentioning
confidence: 99%